Distribution and Specialties of Broadly Versus Narrowly Defined Public Health Nurses Working in Government Settings in the United States, 2022 - Bekemeier, Betty; Kett, Paula M.; Whitman, Greg; Chadwick, Kelly; Edmonds, Joyce K. (American journal of public health (1971), 2025)
Objectives. To estimate the size of the US governmental public health nurse (PHN) workforce by setting and specialty, including those working outside of health departments. Methods. We used 2022 data from the National Council of State Boards of Nursing, representing 2846 registered nurses (RNs) in almost all states, with weights applied. We examined “setting” and “specialty” of PHNs according to broad and more restricted definitions. Results. Using a broad definition, PHNs in government settings made up 3.7% of the RN workforce, and 1.8% when specialty areas were narrowly defined. These percentages varied by state. PHNs working in public health, school health, and correctional health settings largely indicated their specialty practice areas as public health, school health, and “unspecified” rather than more narrow specialty areas. Conclusions. PHNs are a small proportion of the RN workforce. They consider themselves generalists and can be identified by specialty and when working in governmental settings outside of health departments. Public Health Implications. States with few PHNs may be underserving their communities. Better data are needed to understand specific functions and activities of the PHN workforce. ( Am J Public Health. 2025;115(4):536–545. https://doi.org/10.2105/AJPH.2024.307950 )